Our experience in frozen-thaw embryo transfer cycles: The impact of different post-thaw vitrified embryo culture period. - Abdul Wahab, Azantee Yazmie; Ramli, Roszaman; Mohd Bustaman, Siti Khadijah; Mohd Yatim, Hayati (2017)
Vitrification technique has shown great promise for human embryo cryopreservation due to its consistent cryosurvival. The selection of medium and period of post-thawed culture for embryos survival depends on IVF laboratories practice in order to achieve successful pregnancies. The purpose of this study is to determine the influence of post-thawed vitrified embryo in different culture period on the outcome of frozen-thaw embryo transfer (FET) cycles. A total of 28 frozen embryo transfer (FET) cases were conducted at IIUM Fertility Centre, Kuantan, Pahang, Malaysia. The frozen-thaw vitrified embryos were divided into two groups: short culture (<5 hours) and long culture (overnight culture). Eight pregnancies achieved in long culture whereas no pregnancies occurred in short culture. Out of the pregnancies, one had triplet, two twins and others are single babies. As for embryo grade, there is no difference on the clinical outcome. Our results showed that long culture for post-thawed vitrified embryos is more suitable in achieving successful clinical pregnancies.